O processo de geração de inovação baseado nas práticas de gestão de conhecimento em empresas de base tecnológica - Botton, Juliana Santi (2014)
The proposition of this study is based on the Innovation Generation Process (IGP) like basis to technology-based companies (TBC) by the knowledge management practices (KMP). It was understood that, innovation is a knowledge product, consequently, it was proposed to elaborate a theoretical and empirical construction in search of the innovation generation based on the knowledge management (KM), understanding like better way the use of the KMP. Furthermore, the choose of the study s universe, the TBCs, was based in the perspective that they have like synonymous of their work, the innovation. Therefore, this search was structured by the question: How the KMP and their application on technology-based companies, can be organized to allow the development of an Innovation Generation Process? This kind, it was obtained the general objective of this study: Developing a construct of the Innovation Generation Process, based on the Knowledge Management Practices and their application in Technology-based Companies and a) elaborating, by bibliographic study, possible levels and stages in the IGP; b) Listing, by bibliographic study, the KMP that were validates yet, that could be allocated on the IGP; c) identifying on the TBCs, the KMP most used, those whose importance is greater, and, whose would be is the level of each one in the IGP, excluding the rejects and validating other. Developed the theory part of the Construct of IGP, it was applied the questionnaire contain 40 practices and three questions, about Importance, about the frequency and, about the classify of the practices relation to the nine situational variables of IGP. To obtain a return of 47 questionnaires. It was used the test Alpha of Cronbach to confirm the reliability of data to the search. It was applied, the descriptive statistic, compromising like more important practices: Brainstorming or generation of ideas, development and apply of new process and, the corporative University; like more frequents practices: corporative e-mails, enterprise blog and, the social network. In addition, the test of Correlation of Pearson indicated relation of 64, 3% between importance and frequency, and Simple Linear Regression (respecting the regression assumptions) indicated that 42, 3% of the variations at importance are explicated by the variations at frequency. Finally, in relation on the incorporation of the practices to the IGP, they were observed the mean and standard deviation of each practice. Some propositions of analysis were done: a) the Variations coefficient; b) the visual analysis; c) the amplitude and; d) the Factorials Analysis. The first of them was refuted because it didn t supply the proposed objectives; the visual analysis indicated it s applied like auxiliary; the Amplitude Analysis indicated like the best technic to the result obtain, enabling a division with five classifies among the practices: The Primary Practices; The Central Practices; The Superior Practices; The Dispersed Primary Practices and; The Dispersed Superior Practices. The Factorial Analysis corroborated with the Amplitude, dividing the practices on Primary, central and superior practices. In summary, the practices were allocated in chart, showing which practice assist each phase of IGP. The results allow the recommendation the construct another sectors.